Aplikasi Iptek Melalui Pelatihan Penyusunan RAB dan Jadwal Pelaksanaan Pekerjaan Pembangunanan Jalan di Desa Sesaot Lombok Barat - Pathurahman; Hasyim; Rohani; Karyawan, I Dewa Made Alit; Yuniarti, Ratna; Yasa, I Wayan; Negara, I Dewa Gede Jaya (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Sesaot Village is a tourist village in West Lombok Regency, and is the recipient of the Indonesian Tourism Village Award. This village has natural tourist destinations and several artistic and cultural attractions typical of the local community. In order to realize the vision of Sesaot Village as a religious, cultural and independent tourist village, it is very important to pay attention to supporting infrastructure, namely roads. The Sesaot Village has realized government-assisted development funds to carry out road maintenance and construction. This development needs to be closely monitored by the community so that it can achieve targets on time, at the right quality and at the right cost. Supervision can only be carried out if the community has sufficient understanding, especially in budget planning and implementation time plans. Base on current issues, training need be conducted with the following objectives: 1) To give an overview of the complexity involved in creating a budget and schedule for an road infrastructure project; 2) To impart knowledge on the meticulous, accurate, and precise preparation of a Budget Plan (RAB) and timetable. Goal-achieving strategies cover everything from implementation phases to work processes and evaluation. The process of implementation is divided into three primary stages: preparation, implementation, and evaluation. Preliminary survey/observation and socialization are two steps in the preparation stage. The preparation of participant materials and training tools, training, and mentorship activities, as well as the service team's discussion and consideration of the activities' execution, are all included in the execution Stage. Community service activities in the form of training carried out for one day, attended by 20 participants, received a good response from the Village Government and the community. The planned events transpired without a hitch and significantly influenced the participants' capacity to draft the RAB and timetable for the road project's implementation. This is shown by the increase in the average pre-test to post-test scores of most participants. It is hoped that the knowledge acquired would serve for being allowed to take part in future monitoring the road construction program in Sesaot Village.